Pengembangan Kartu Kuartet sebagai Media Pembelajaran pada Materi Aljabar Terintegrasi Kearifan Lokal Magepanda - Anomeisa, Agnesia Bergita; Ernaningsih, Dian; Piterson, Romanus; Wahyuningsih, Wahyuningsih; Safrudin, Nurfitriah (Educatio, 2024)
This research aims to explore how to develop quartet cards as a learning media for algebra material integrated with the local wisdom of Magepanda. The problem addressed in this study is the difficulty students face in understanding the implementation of algebra concepts in everyday life, coupled with the low availability of supportive mathematics learning facilities in schools, which hinders the use of technology-based learning media. Therefore, this research seeks to address these issues by integrating algebra material into a quartet card game that includes information about Magepanda's local culture, allowing students to learn while playing anywhere and anytime, without relying on electricity and internet access. The methodology used in this research is a type of Research and Development (R&D) with the 4D model (Define, Design, Development, and Dissemination). In the Define stage, a needs assessment and identification of Magepanda's local wisdom relevant to algebra concepts were conducted. The Design stage involved the initial design of the quartet cards, incorporating relevant local wisdom elements. The Development stage included the creation of a prototype of the quartet cards, validation of the content by experts, and revisions based on feedback. The Dissemination stage involved sharing the results with local mathematics teachers for further implementation. The research findings received positive reactions from users of the learning media, with product validation results classified as Highly Feasible. By playing the developed quartet cards, students became more enthusiastic about learning algebra and were able to relate the material to the context of their daily lives.